Квантово-химическое исследование комплекса хлорид лития/этилметилсульфон с помощью ограниченного метода Хартри-Фока - А. С. Мхитарян (ՀՀ ԳԱԱ հրատ.)
Система хлорид лития/этилметилсульфон исследована ограниченным методом Хартри-Фока (RHF/6-311++G(d,p)) с целью установления структурных и спектральных параметров этой системы. Проведен сравнительный анализ полученных результатов с расчетными данными системы LiCl/диметилсульфон. Показано наличие двух стабильных комплексов 1:1 LiCl:этилметилсульфон, а также одного переходного состояния. Установлено, что интенсивность валентных колебаний CH и SO групп зависит от типа структуры комплекса LiCl:этилметилсульфон: такой эффект наблюдается и у диметилсульфона, и у диэтилсульфона. Разность свойств этих структур объясняется колебательным эффектом Штарка, а не только специфичными взаимодействиями. Լիթիումի քլորիդ/էթիլմեթիլսուլֆոն համակարգի կառուցվածքը և տատանողական սպեկտրները ուսումնասիրվել են Հարտրի-Ֆոկի (RHF/6-311++G(d,p)) սահմանափակ մեթոդի օգնությամբ: Հաշվարկները ցույց են տվել երկու կայուն 1:1 LiCl:էթիլմեթիլսուլֆոն կոմպլեքսների, ինչպես նաև մեկ անցողիկ վիճակի գոյությունը: Ցույց է տրվել, որ CH և SO EUμերի վալենտային տատանումների ինտենսիվությունները կախված են 1:1 լիթիումի քլորիդ/էթիլմեթիլսուլֆոն կոմպլեքսների կառուցվածքից: Այդ կառուցվածքների հատկությունների տարբերությունը բացատրվում է Շտարկի էֆեկտով: Ստացված արդյունքները համեմատվել են LiCl/դիմեթիլսուլֆոնի և LiCl/դիէթիլսուլֆոնի տվյալների հետ: In recent years lithium-ion batteries have been widely applied for portable electronic devices such as cellular phones and personal computers. Sulfones are dipolar aprotic solvents, which are used in lithium-ion batteries because of their high resistivity to electrode materials and ability to ensure high speed of electrode process. The aim of this work is the study of the local structures of LiCl in ethyl methyl sulfone (EMSO2) using quantum chemical calculations. All calculations have been carried out using the Gaussian 09 software package. Optimization of the molecular structure of isolated molecule of EMSO2 and that of the complex 1:1 LiCl:EMSO2 in their ground states in the gas phase was performed using restricted Hartree-Fock (RHF) method combined with 6-311++G(d,p) extended basis set including polarization and diffuse functions. The assignment of theoretical vibrational modes was performed by GaussView 5.0, which gives a visual representation of vibrational modes. The structural and spectral parameters of LiCl/ethyl methyl sulfone system were established. The calculations show the existence of two stable 1:1 LiCl:ethyl methyl sulfone structures and one transition state. The energy minima and transition state structure were verified by vibrational analysis. Energy minima were confirmed by the absence of imaginary vibration frequency. In the case of transition state one imaginary mode was observed. It was shown that intensity of the CH and SO stretching vibrations to the interaction between LiCl and sulfone strongly depends on the structure of the complex. The difference in spectral features is explained in the frame of vibrational Stark effect. The obtained results have been compared with those for LiCl/dimethyl sulfone and LiCl/diethyl sulfone system.
Keywords: Physical Chemistry